2020
DOI: 10.1016/j.biopsycho.2020.107845
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in emotional concordance

Abstract: Emotions involve response synchronization across experiential, physiological, and behavioral systems, referred to as concordance or coherence. Women are thought to be more emotionally aware and expressive than men and may therefore display stronger response concordance; however, research on this topic is scant. Using a random-order film-average design, we assessed concordance among experiential (arousal, valence), autonomic (electrodermal activity, heart rate, preejection-period, respiratory-sinus-arrhythmia),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 95 publications
5
20
0
Order By: Relevance
“…It is also worth noting that for the BAI, the latent inter-factor correlations indicated that the panic, neurophysiological, and autonomic factors were more strongly correlated with the subjective anxiety factor in women than in men. This result is particularly interesting considering findings that concordance between physiological and subjective components of emotional responding were more strongly linked in women than in men in laboratory studies (e.g., Rattel et al, 2020). The present findings add to this literature by suggesting that these gender differences are reflected at the level of self-reported symptoms as well.…”
Section: Discussionsupporting
confidence: 76%
“…It is also worth noting that for the BAI, the latent inter-factor correlations indicated that the panic, neurophysiological, and autonomic factors were more strongly correlated with the subjective anxiety factor in women than in men. This result is particularly interesting considering findings that concordance between physiological and subjective components of emotional responding were more strongly linked in women than in men in laboratory studies (e.g., Rattel et al, 2020). The present findings add to this literature by suggesting that these gender differences are reflected at the level of self-reported symptoms as well.…”
Section: Discussionsupporting
confidence: 76%
“…They may also have been more impacted by the higher number of deaths and difficulties during the crisis. Women show greater psychophysiological concordance and consistency than men [ 59 ], and may therefore present more psychological vulnerability [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the extent to which perceivers' physiology links up with targets' emotional arousal should be associated with greater empathic accuracy for targets' emotional arousal. Future work might try to capture ratings of both emotional valence and arousal to examine whether the effects do replicate (c.f., Rattel, Mauss, Liedlgruber, & Wilhelm, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%